Pengaruh Tekanan Anggaran Waktu, Locus of Control, Kompleksitas Tugas dan Turnover Intention Terhadap Perilaku Disfungsional Auditor Pada Kantor Akuntan Publik di Provinsi Bali - Dewa Ayu Shiinta Widhiaswari; I Made Wianto Putra; Ni Nyoman Sri Rahayu Damayanti (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
The purpose of this study was to determine the Time Budget Pressure, Locus of Control, Task Complexity and Turnover Intention affect the dysfunctional behavior of auditors at KAP in Bali Province. The number of samples in this study were 82 auditors. The sampling technique used is a non-probability sampling method. The data analysis technique in this study is multiple linear regression analysis. Based on the results of the analysis, it was found that Time Budget Pressure and Locus Of Control had a negative effect on the Auditor's Dysfunctional Behavior at the Public Accounting Firm in Bali Province. Task Complexity and Turnover Intention have a positive effect on the Dysfunctional Behavior of the Auditor at the Public Accounting Firm in Bali Province.